IMPLEMENTASI PEMBELAJARAN COOPERATIFE LEARNING DALAM MENINGKATKAN MOTIFASI BELAJAR PENDIDIKAN AGAMA ISLAM DI SD - Yayuk Hidayati; Umi Karimatul Azizah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT slamic Religious Education at the elementary school level is expected not only to deliver religious knowledge but also to foster students’ active engagement in the learning process. Preliminary observations at SDN Kaliboto Kidul 02 revealed that some students demonstrated limited participation during classroom activities, particularly in discussions, expressing opinions, and involvement in learning tasks. This condition prompted an examination of the implementation of Cooperative Learning to better understand how learning motivation develops within Islamic Religious Education. The study employed a descriptive qualitative approach using observations, interviews, and documentation involving the principal, the Islamic Religious Education teacher, and students as research participants. Data were analyzed through data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure the credibility of the findings. The findings indicate that the implementation of Cooperative Learning goes beyond merely organizing students into groups; it creates an interactive learning environment that encourages the exchange of ideas, collaboration, and active participation. Such learning dynamics contribute to the development of students’ learning motivation, as reflected in increased participation, confidence in expressing opinions, responsibility in completing tasks, and enthusiasm for learning activities. Therefore, the primary contribution of Cooperative Learning lies in its ability to create a participatory learning experience that positions students as active learners while simultaneously supporting the development of their social skills in Islamic Religious Education. ABSTRAK Pembelajaran Pendidikan Agama Islam di sekolah dasar tidak hanya dituntut mampu menyampaikan materi keagamaan, tetapi juga membangun keterlibatan peserta didik dalam proses belajar. Kondisi awal di SDN Kaliboto Kidul 02 memperlihatkan bahwa sebagian siswa masih menunjukkan partisipasi yang terbatas selama pembelajaran, terutama dalam diskusi, penyampaian pendapat, dan keterlibatan pada aktivitas kelas. Situasi tersebut mendorong kajian mengenai implementasi Cooperative Learning sebagai upaya memahami bagaimana motivasi belajar berkembang dalam pembelajaran Pendidikan Agama Islam. Penelitian ini dilakukan dengan pendekatan kualitatif deskriptif melalui observasi, wawancara, dan dokumentasi yang melibatkan kepala sekolah, guru Pendidikan Agama Islam, serta siswa. Data dianalisis melalui proses reduksi, penyajian, dan penarikan makna dengan dukungan triangulasi sumber dan teknik untuk menjaga kredibilitas temuan. Kajian ini memperlihatkan bahwa penerapan Cooperative Learning tidak hanya menghadirkan aktivitas belajar kelompok, tetapi juga membentuk ruang interaksi yang memungkinkan siswa saling bertukar gagasan, bekerja sama, dan terlibat secara lebih aktif dalam pembelajaran. Dinamika tersebut berkontribusi pada tumbuhnya motivasi belajar yang tercermin melalui meningkatnya partisipasi, keberanian menyampaikan pendapat, tanggung jawab terhadap tugas, dan antusiasme mengikuti pembelajaran. Dengan demikian, kontribusi utama Cooperative Learning terletak pada kemampuannya menciptakan pengalaman belajar yang partisipatif sehingga siswa menjadi lebih aktif sekaligus memperoleh kesempatan mengembangkan keterampilan sosial dalam pembelajaran Pendidikan Agama Islam.